THE IMMERSION EFFECT OF MIXTURE OF SMALL WHITE GINGER AND GARLIC EXTRACT ON COLOR CHANGES OF ACRYLIC PLATE - Dea Pengasih; Debby Saputera; Bayu Indra Sukmana (Dentino : Jurnal Kedokteran Gigi, 2020)
Background: Heat cured acrylic resin is often used as a component of denture. One of the heat cured acrylic resin properties is water absorption that affects the change in acrylic color. An alternative using natural compound to minimize side effect is arising when compared to synthetic materials. A mixture of  small white ginger and garlic extract can be used as natural denture cleanser. Objective: This study aimed to know the color changes of heat cured resin plate that immersed in a mixture of 70% small white ginger and 10% garlic extract. Method: This was a true experimental study with pretest and posttest with control group design, using simple random sampling. The sample was cylindrical acrylic with 15 mm diameter and 2 mm thickness. The research was done using 18 samples heat cured acrylic resins which were divided into 3 groups, the mixture of 70% small white ginger and 10% garlic extract, alkaline peroxide, and distilled water. The color change of the sample was tested using digital analysis tools set. Results: The mean value of color changes in heat cured acrylic resin plate after immersion in a group of mixed extracts, alkaline peroxide, and distilled water were 6.23, 3.65 and 2.48. Data were analyzed using  One Way ANOVA parametric test and Dunnet T3 Post Hoc test. Conclusion: There is a difference in color changes of heat cured resin plate after the immersion in a mixture of extract and alkaline peroxide. Acrylic resin that immersed in mixed extract demonstrates a higher value of color change.